A Novel Ternary Content Addressable Memory Cell - Datti, VenkataRamana; Sridevi, Dr.P.V. (International Journal of Engineering and Technology, 2018)
Ternary content addressable memories (TCAM) are used for parallel searching. The parallel searching, results high speed but consumes more power. For higher search speed applications, NOR type matchline TCAMs are useful. The NOR type matchline TCAM needs high power; therefore, the power reduction is the major objective of many reported designs. Here, a novel TCAM cell is proposed. The proposed Ternary CAM cell power consumption is 32% lesser than the NOR type matchline TCAM cell. Simulations are performed using cadence 45-nm technology.